2006
DOI: 10.4028/www.scientific.net/kem.302-303.211
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shrinkage Reduce Agent on Early Age Autogenous Shrinkage of Concrete

Abstract: Based on designed and manufactured test equipment of concrete early age shrinkage, the influence of shrinkage reduce agent (SRA) on early age autogenous shrinkage of concrete was researched. The test results show that early age autogenous shrinkage of concrete was reduced with SRA added and the shrinkage-reducing ratio increased with concrete strength grade heightened. SRA could also greatly reduce early age autogenous shrinkage of concrete added with pulverized ly ash or slag. Superplasticizer would increse e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, a steel mold located on the concrete surface can exert frictional resistance on the concrete, which influences the measurement of deformation at early age. Flexible corrugated pipes are used to eliminate it as the stiffness of the axial direction was negligible compared with the stiffness of radial direction and the change in volume was replaced by the change in length [8]. Based on Figure 7, flexible corrugated pipes can be used to replace the steel mould.…”
Section: Automatic Measurement Methods On Concrete Deformation At Ear...mentioning
confidence: 99%
“…However, a steel mold located on the concrete surface can exert frictional resistance on the concrete, which influences the measurement of deformation at early age. Flexible corrugated pipes are used to eliminate it as the stiffness of the axial direction was negligible compared with the stiffness of radial direction and the change in volume was replaced by the change in length [8]. Based on Figure 7, flexible corrugated pipes can be used to replace the steel mould.…”
Section: Automatic Measurement Methods On Concrete Deformation At Ear...mentioning
confidence: 99%
“…A study by Montani [64] has shown that using shrinkage reducing admixtures in plain concrete can result in decreasing the drying shrinkage by about 30%. Combining shrinkage reducing admixtures with pulverized fuel ash or slag leads to a reduced early age autogenous shrinkage [65]. Indeed, different water reducers were tested in terms of their influence on the resistance to plastic shrinkage, and all types of water reducer exhibited satisfactory performance.…”
Section: Plain Concrete With Admixturesmentioning
confidence: 99%
“…Published literature [1,2] indicates that different varieties of admixtures have a significant effect on concrete shrinkage rate. The literature [3,4] studied the influence of water reducer on volume stability of concrete, which showed that water reducer could increase the shrinkage of concrete, especially, the greater increase in shrinkage within 24 hours. In this paper, test carried out in accordance with the China Civil Engineering Society standard CCES 01, Durability Design of Concrete Structures and Construction Guidelines, which appendix A "test methods and evaluation of concrete cracking resistance" recommended flat-panel test method [5].…”
Section: Introductionmentioning
confidence: 99%